Über Sprachen aus der Perspektive von Gymnasiast*innen aus Slowenien und aus der Slowakei - Lipavic Oštir, Alja (2021)
The monograph answers questions about the perception and viewpoints of languages and language varieties among high school students from Slovakia and Slovenia. With the help of surveys and language cards general linguistic, socioand psycholinguistic knowledge, stereotypes, preferences and identifications with languages and language varieties are analyzed quantitatively and qualitatively. The analyses show the following results: Slovene and Slovak as L1 of most high school students have a prestigious position, with high school students from Slovene strongly identifying with (traditional) regions. Neighboring countries and languages are less important in the linguistic world of high school students, although at the same time, a kind of hidden multilingualism can be observed. High school students from both countries share the same stereotypes about some European languages, and they agree with the same prejudices, even Eurocentric ones. Aesthetically, they prefer Romance languages, and they have little general linguistic and psycholinguistic knowledge as well as relatively little sociolinguistic knowledge. Based on all the results, recommendations for language and school policy in both countries have been made.